Efficient transformation of CO2 to cyclic carbonates using bifunctional protic ionic liquids under mild conditions. Issue 12 (3rd June 2019) - Meng, Xianglei; Ju, Zhaoyang; Zhang, Suojiang; Liang, Xiaodong; von Solms, Nicolas; Zhang, Xiaochun; Zhang, Xiangping
Abstract : Bifunctional protic ionic liquids were prepared and they showed high activity for conversion of CO2 with epoxides at mild temperature (30–50 °C) and 1 bar CO2 . Abstract : A series of 1, 8-diazabicyclo-[5.4.0]undec-7-ene (DBU) based bifunctional protic ionic liquids (DBPILs) were easily prepared by acid–base reactions at room temperature. They were used to catalyze the cycloaddition reaction of CO2 with epoxides under mild conditions. As a metal free catalyst, the best DBPIL showed a 92% yield of products within 6 hours at 30 °C and 1 bar CO2 without any solvents and co-catalysts. It could afford carbonates in good yields with broad epoxide substrate scope and CO2 from simulated flue gas (15% CO2 /85% N2 ). IR spectroscopy and DFT studies were carried out to investigate the mechanism of the cycloaddition reaction. The results showed that the DBPILs could activate both CO2 and epoxides by alkoxy anions and powerful hydrogen-bonding, which was well consistent with experiments.